1975
DOI: 10.1159/000214090
|View full text |Cite
|
Sign up to set email alerts
|

Cyclical Changes in Coagulation Factors Associated with the Use of Progestational Agents

Abstract: The activity of factors II, VII, VIII, IX, X and fibrinogen and factor VIII antigen levels were followed during a single menstrual cycle in three females using oral contraceptive agents, and in two controls. Marked cyclical variation occurred in the activity of factor VII and VIII, but not in factor VIII antigen levels. Less marked changes occurred in factor II and fibrinogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
1996
1996

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Sequential studies performed in our laboratory [16] have demonstrated marked variation in the level of certain clotting factors, espe cially factors VII and VIII throughout an oral contraceptive cycle. It is therefore important that the time of sampling in the menstrual cycle should be standard.…”
Section: Discussionmentioning
confidence: 99%
“…Sequential studies performed in our laboratory [16] have demonstrated marked variation in the level of certain clotting factors, espe cially factors VII and VIII throughout an oral contraceptive cycle. It is therefore important that the time of sampling in the menstrual cycle should be standard.…”
Section: Discussionmentioning
confidence: 99%